HUMAN NATURE, EQUALITY AND VIOLENCE: HOBBES A POLITICAL REVIEW - Cagmar, Mehmet Sirin (Univ Estadual Ceara-Uece, 2024)
This article discusses the effects of the political structures that emerged with the civilization process on human nature in Hobbes. Hobbes constructs the state of nature in an area where humans can live their nature completely freely. Although this situation creates a certain area of freedom for human nature, when it comes to social relations, this freedom endangers the lives of all people. As is known, Hobbes' solution on this issue is to build political structures such as states that will benefit everyone, rather than people acting as in the state of nature. However, what I am trying to draw attention to here is whether human nature is dispensable with this transition. My main purpose in this article will be to show that even if there is a change in human position, his nature repositions itself as a fundamental determinant that in a sense manages and shapes all processes within political structures under different appearances, as in the state of nature. In the article handled for such a purpose, it is shown that human nature is no longer possible to remain in its pure form and has transformed into something that we can deal with through a political relationship. The basic view defended in this article is that with this new situation, which we can call the emergence of political nature, human nature emerges as a new force shaping the entire political field.
Keywords: Human Nature; Equality; Violence; Political Violence